Aberrant expression of the neuronal transcription factor FOXP2 in neoplastic plasma cells: Research paper - Campbell, A; Lyne, L; Brown, P; Launchbury, R; Bignone, P; Chi, J; Roncador, G; Lawrie, C; Gatter, K; Kusec, R; Banham, A (2010)
FOXP2 mutation causes a severe inherited speech and language defect, while the related transcription factors FOXP1, FOXP3 and FOXP4 are implicated in cancer. FOXP2 mRNA and protein expression were characterised in normal human tissues, haematological cell lines and multiple myeloma (MM) patients' samples. FOXP2 mRNA and protein were absent in mononuclear cells from different anatomical sites, lineages and stages of differentiation. However, FOXP2 mRNA and protein was detected in several lymphoma (8/20) and all MM-derived cell lines (n = 4). FOXP2 mRNA was expressed in bone marrow samples from 96% of MM patients (24/25), 66·7% of patients with the pre-neoplastic plasma cell proliferation monoclonal gammopathy of undetermined significance (MGUS) (6/9), but not in reactive plasma cells. The frequency of FOXP2 protein expression in CD138+ plasma cells was significantly higher in MGUS (P = 0·0005; mean 46·4%) and MM patients (P ≤ 0·0001; mean 57·3%) than in reactive marrows (mean 2·5%). FOXP2 (>10% nuclear positivity) was detectable in 90·2% of MM (55/61) and 90·9% of MGUS (10/11) patients, showing more frequent expression than CD56 and labelling 75% of CD56-negative MM (9/12). FOXP2 represents the first transcription factor whose expression consistently differentiates normal and abnormal plasma cells and FOXP2 target genes are implicated in MM pathogenesis. © 2010 Blackwell Publishing Ltd.